TO STRATEGY OF ORGANIZATION CONTINUOUS EDUCATION IN UKRAINE - Дзвінчук, Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
It is proved that new century has begun transition from industrial to nanotechnologies. The higher education of Ukraine should be guided not by struggle against corruption but on continuous training of all active population on preparation of experts on nanotechnologies, capable to design and make androrobots and other techniques of middle ХХІ of a century.